2004
DOI: 10.1038/nature02280
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure and mechanism of a bacterial fluorinating enzyme

Abstract: Fluorine is the thirteenth most abundant element in the earth's crust, but fluoride concentrations in surface water are low and fluorinated metabolites are extremely rare. The fluoride ion is a potent nucleophile in its desolvated state, but is tightly hydrated in water and effectively inert. Low availability and a lack of chemical reactivity have largely excluded fluoride from biochemistry: in particular, fluorine's high redox potential precludes the haloperoxidase-type mechanism used in the metabolic incorpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
296
1
11

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 315 publications
(320 citation statements)
references
References 28 publications
7
296
1
11
Order By: Relevance
“…Ekstrom et al, 2002;Evans et al, 2002;Gadola et al, 2002;Hall et al, 2002;Matern et al, 2003;Nicolet et al, 2003;Zavala-Ruiz et al, 2003;Dong et al, 2004).…”
Section: Testing In X-ray Refinementunclassified
“…Ekstrom et al, 2002;Evans et al, 2002;Gadola et al, 2002;Hall et al, 2002;Matern et al, 2003;Nicolet et al, 2003;Zavala-Ruiz et al, 2003;Dong et al, 2004).…”
Section: Testing In X-ray Refinementunclassified
“…Enzymatic processes exist that form and break the CÀ ÀF bonds present in these compounds. 13 On the other hand, no natural perfluorocompounds or moieties have, as yet, been found. Consequently, nature did not bother to develop the enzymatic machinery that would allow for their generation and recycling.…”
Section: Perfluorocarbon Chemistry and Lifementioning
confidence: 99%
“…A stereochemical study that involved (5′S)-[5′-2 H]-SAM has indicated that the C-F bond of 5′-FDA replaces the C-S bond of SAM with an inversion of configuration. [11,12] This observation, as well as a theoretical study [13] and structural analysis [10] all suggest an S N 2 reaction mechanism for the fluorinase. Despite the high bonddissociation energy of the C-F bond (the strongest bond in organic chemistry [14] ), we herein report that the fluorinase operates in the reverse direction and that it utilizes a chloride ion.…”
mentioning
confidence: 91%
“…[3][4][5] After depurination, 5′-FDA is metabolized first to 5-fluoro-5-deoxyribose-1-phosphate (5′-FRP) [6] and then to fluorocetaldehyde. [7] Fluoroacetaldehyde is converted separately into fluoroacetate [8] and 4-fluorothreonine [9] (Scheme 1).The fluorination enzyme, which has been the subject of a recent structural study, [10] has been isolated and fully characterized, the gene has been cloned, and the enzyme has been overexpressed. A stereochemical study that involved (5′S)-[5′-2 H]-SAM has indicated that the C-F bond of 5′-FDA replaces the C-S bond of SAM with an inversion of configuration.…”
mentioning
confidence: 99%
See 1 more Smart Citation